1995
DOI: 10.1038/373681a0
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the chemical reactivity of individual molecules of an enzyme

Abstract: Much attention has been focused recently on the detection and physical characterization of individual molecules. Using such methods to study the chemical properties, such as reactivity, of single molecules offers the potential to investigate how these might vary from molecule to molecule, and for individual molecules as a function of time. The complex structures of biomolecules such as enzymes make them particularly attractive targets for studying how subtle changes or differences at the molecular level might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
300
2
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(326 citation statements)
references
References 19 publications
21
300
2
3
Order By: Relevance
“…S2). Thus, in the present study, we could not detect intermolecular (static) variation as in other single molecule enzyme studies (14)(15)(16). Instead, the variability observed here is due to the limited number of events we could record from individual molecules.…”
Section: Two Dwell Time Populations Neither Resulted From Adp Accumulcontrasting
confidence: 63%
See 2 more Smart Citations
“…S2). Thus, in the present study, we could not detect intermolecular (static) variation as in other single molecule enzyme studies (14)(15)(16). Instead, the variability observed here is due to the limited number of events we could record from individual molecules.…”
Section: Two Dwell Time Populations Neither Resulted From Adp Accumulcontrasting
confidence: 63%
“…variation seen for other enzymes (14)(15)(16). Kinetic modeling suggested that the two dwell time populations originate from two active site conformers with different ATP binding features.…”
Section: Significancementioning
confidence: 86%
See 1 more Smart Citation
“…Further analysis using higher order correlation functions did not help discrimination between this simple model involving two alternative conformations and another involving a continuum of conformers. 195 This seminal study definitely confirmed the existence of static and dynamic heterogeneity in enzymes, 196,197 illustrating the power of single-molecule fluorescence studies for elucidating enzymatic reaction mechanisms inaccessible via ensemble methods.…”
Section: Quenching Due Tomentioning
confidence: 85%
“…Ideally, each transition to another inhibition state will be reflected in a 25% change of substrate turnover. It is known, however, that the individual activities of different enzyme molecules can vary by up to a factor of four, even without inhibitor (1,3), and it is possible that the activity of an individual enzyme may fluctuate upon inhibitor binding and release. In this case, it would not be possible to distinguish the different states of inhibition depicted in Scheme 1 by comparing the substrate turnover…”
mentioning
confidence: 99%